2015
DOI: 10.1177/1971400915610699
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Canadian CT head rule in predicting positive findings on CT of the head of patients after mild head injury in a large trauma centre in Saudi Arabia

Abstract: The level of education regarding the CCHR was found to be optimal among emergency physicians using a case-based scenario survey. The CCHR was found to have a poor compliance potential in the busy ED of our trauma centre and the prevalence of unjustified cranial CT scans remained high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 12 publications
(14 reference statements)
2
12
0
1
Order By: Relevance
“…We demonstrated a sensitivity of 70% if the rule was applied. Similar studies have shown a 66.67% sensitivity (13) which is comparative to this study. The rule was shown to have a negative predictive value 87.5%.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…We demonstrated a sensitivity of 70% if the rule was applied. Similar studies have shown a 66.67% sensitivity (13) which is comparative to this study. The rule was shown to have a negative predictive value 87.5%.…”
Section: Discussionsupporting
confidence: 88%
“…In developed countries, the use of CT scans in traumatic brain injuries is very common but the yield for intracranial injuries is relatively low at 0.7-3.7% (7,13). This represents a cost of 135-216 million dollars annually (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parte deles analisou somente a diretriz CCHR. Arab et al ( 2015) 9 aplicaram retrospectivamente a diretriz CCHR em 368 pacientes atendidos com TCE leve e que, na ocasião de seu atendimento, haviam realizado tomografia de crânio. Após essa análise, verificaram que a prevalência de tomografias não justificadas, segundo a diretriz, foi de 61,8%.…”
Section: Discussionunclassified
“…Multiple validated clinical decision rules have been established to standardize and increase the efficiency of CT indication in patients after mTBI [5][6][7][8][9][10]. The Canadian CT Head Rule (CCHR) is the most common and has been found to be highly sensitive for detecting intracranial lesions; however, its specificity varies widely [10][11][12][13]. Other rules, such as the New Orleans criteria, the NICE, the Scandinavian rules, and NEXUS-II, based on different clinical and demographic indicators for imaging, have also demonstrated their validity and generalizability [9,14].…”
Section: Introductionmentioning
confidence: 99%